2022 Fitness Trends from Around the Globe. (January 2022) - Kercher, Vanessa M.; Kercher, Kyle; Bennion, Trevor; Levy, Paul; Alexander, Chris; Amaral, Paulo Costa; Li, Yong-Ming; Han, Jia; Liu, Yang; Wang, Ran; Huang, Hai-Yan; Gao, Bing-Hong; et al.
Abstract : Supplemental digital content is available in the text. Apply It!: From this article, the reader should be able to Identify top 20 fitness trends for Australia, Brazil, China, Europe, Mexico, Spain, and the United States. Recognize individual and unique fitness trends represented within Australia, Brazil, China, Europe, Mexico, Spain, and the United States.